Evidence-based evaluation, a new approach to evaluation by competences - Huerta Rosales, Moisés (2018)
The objective of this paper is to explain the methodological design of competency assessment, based on evidence as a new way of assessing performance in a more objective and contextual way.This proposal is the product of the theoretical review and empirical experiences that combined with critical analysis allows establishing a more objective methodology resource to evaluate competences, different from the traditional cognitive assessment.Performance-based evaluation articulates planning, execution and evaluation, in order to achieve coherence between what was planned, what was evaluated and what was learned. In the planning it relates the levels of competition with the contents and indicators of achievement; then they articulate with instruments, the evidences of knowing, doing, being and of product.Finally, all the components are integrated, for their execution, allowing showing the didactic sequence of an authentic evaluation, based on observable and measurable evidences.